A Spitzer IRAC Census of the Asymptotic Giant Branch Populations in Local Group Dwarfs. I. WLM - Jackson, Dale C; Skillman, Evan D; Gehrz, Robert D; Polomski, Elisha; Woodward, Charles E (The Astrophysical journal, 2007)
We present Spitzer IRAC observations at 3.6 and 4.5 km along with optical data from the Local Group Galaxies Survey to investigate the evolved stellar population of the Local Group dwarf irregular galaxy WLM. These observations provide a nearly complete census of the AGB stars. We find that 39% of the infrared-detected AGB stars are not detected in the optical data, even though our 50% completeness limit is 3 mag fainter than the red giant branch tip. An additional 4% of the infrared-detected AGBs are misidentified in the optical, presumably due to reddening by circumstellar dust. We also compare our results with those of a narrowband optical carbon star survey of WLM and find the latter study sensitive to only 18% of the total AGB population. We detect objects with infrared fluxes consistent with them being mass-losing AGB stars and derive a present-day total mass-loss rate from the AGB stars of = (0.7-2.4) x 10 super(-3) M yr super(-1). The distributions of mass-loss rates and bolometric luminosities of AGBs and red supergiants are very similar to those in the LMC and SMC, and the empirical maximum mass-loss rate observed in the LMC and SMC is in excellent agreement with our WLM data.